Food safety, risk intelligence and benchmarking - Charlebois, Sylvain (John Wiley & Sons, 2017)
This book comprehensively argues for more future benchmarking between nations. Since the initial food safety benchmarking report was published in 2008, the sharing of data and protocols among nations has dramatically increased. It was intended to identify and evaluate common elements among global food safety systems.